Global Gender Inequality: Review and Analysis (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
Gender inequality is one of the most pervasive forms of inequality in the world.This is not just because, it is present in most societies, but also because; it cuts across otherforms of inequalities in human endeavour. This paper shows that, the geography of genderinequality reflects systematic regional differences in institutions of Kinship and family, thehousehold patterns they have given rise to and the associated gender division of resourcesand responsibilities. Thus, a great deal of human behaviour is not the result of individualpreferences. Rather, it is governed by institutional rules, norms and conventions that havepowerful material effects in people’s lives. These rules may be written or unwritten, explicitor implicit, statutory or non-statutory, but sanctified by religion, upheld by convention orembodied in the standards of family, community and society
Keywords: eradication, gender, global, globalization and inequality.